Masculinity and its role in gender-based violence in South Africa - Davhana-Ngwenya, Vhugala (University of the Witwatersrand, Johannesburg, 2024)
This study investigates ways in which men construct masculinity and understand its role in gender-based violence. An increased interest in studying masculinity and its construction suggests that there are different ways in which men express their masculinities. 11 males over the age of 18 participated in the study. A semi-structured interview schedule was used to guide one on one interviews that were used to collect data. The interviews were recorded and transcribed for easy analysis. Thematic analysis was used to analyse the data through identifying, analysing, and reporting repeated themes. Specifically, four themes were identified in this study: (1) Constructions of traditional masculinity, (2) Construction of gender-based violence, (3) Role models and (4) Proposed interventions for gender- based violence. The findings suggest that participants have a negative view towards the traditional ideology of masculinity and conventional masculinity. For most of the participants’ influential role models were predominantly male figures who held positions of authority in their households or communities while for other media emerged as a significant role model. The participants understood the impact of GBV and its far-reaching consequences on its victims. The research will contribute to the field of psychology in the understandings of constructions of masculinity and its role in Gender Based Violence.
A research report submitted in fulfillment of the requirements for the Master of Arts in Social and Psychological Research in Psychology, In the Faculty of Humanities, School of Human and Community Development, University of the Witwatersrand, Johannesburg, 2024
Keywords: UCTD; Gender; Gender-based violence; Hegemonic masculinity; Masculinity; Men; Patriarchy; South Africa; SDG-5: Gender equality